VOLUNTARY DISCLOSURE, EARNINGS RESPONSE COEFFICIENT AND EARNINGS PERSISTENCE - Yessy Aryanti Lestari (Universitas Muhammadiyah Malang, 2020)
One of management credibility aspect showed by extent voluntary information disclosed. Management who more credible do more voluntary disclosure. Management use voluntary disclosure as tools to inform good signal happening to all stakeholders, include good earnings quality. This study examine the association of voluntary disclosure to earnings response coefficient (ERC) and earning persistence as earnings quality. Study uses 274 samples of listed firms across different industries in Indonesia, excluding financial industry for the financial period 2015. Ordinary least square (OLS) cross-sectional method is implemented to test the research hypotheses. The results of hypothesis test of the study exhibit a significant negative association between voluntary disclosure to ERC. This study also found no association statistically between voluntary disclosure to earnings persistence. This research conducted for one period, so for future research should to extent year observations. The study also conducted additional testing of disclosures based on disclosure criteria. This test was conducted to determine the type of voluntary disclosure that has a significant influence on the dependent variable of the study, ERC and earnings persistence.Keywords: Earnings Responses Coefficient, Voluntary Disclosure, Earnings Persistence